Estrutura matrilinear de populações ex situ e in situ do mico leão preto (Leontopithecus chrysopygus Mikan, 1823) e insights para seu manejo - Modena, Pamela Zaganin (Universidade Federal de São Carlos, 2021)
The Leontopithecus chrysopygus species, popularly known as the black lion tamarin (MLP), has been suffering from the fragmentation of its natural habitat, which limits gene flow and results in a decrease in genetic variability and an increase in inbreeding within populations. The genetic-population study and the establishment of genetic diversity parameters, based on molecular data from mitochondrial DNA, allow the characterization of the structure and historical genetic diversity within and between populations, and this information is important to help manage the species and maintain genetic variation both in free-living and captive populations. In this work, the matrilineal structure of ex situ and in situ groups was evaluated with the aim of generating insights to support decisions on long-term management and conservation of the species. Additionally, pedigree data were analyzed to establish kinship relationships among captive animals. The control region (D-loop) of the mitochondrial genome was evaluated in 43 MLPs from five free-living populations and 32 captive individuals kept at the Fundação Parque Zoológico de São Paulo (FPZSP, SP); 19 individuals at the Rio de Janeiro Primate Center and 20 at the Durrell Wildlife Conservation Trust (DWCT, Jersey). The generated sequences were analyzed using different computational tools to characterize the haplotype diversity and genetic structure of the evaluated groups. Pedigree analysis showed lower relatedness values ​​in FPZSP than in CPRJ and DWCT. The analysis of mitochondrial data showed a total of seven haplotypes, only three of them (H1, H2 and H3) being shared between free-living and captive individuals. The mean value of haplotypic diversity (Hd) was higher in free-living (0.752) than in captivity (0.589). The existence of unique haplotypes in FPZSP, in addition to the low haplotype diversity observed in DWCT and its absence in CPRJ, highlights the urgent need for a metapopulation management that aims to preserve a broader base of matrilineal genetic diversity in these two institutions. The presence of a unique haplotype in FPZSP also indicates the need to expand the analyzes in in situ populations. On the other hand, unique haplotypes were found in in situ populations, indicating that contemporary ex situ populations do not retain historical matrilineal diversity representative of the free-living populations evaluated so far. This study brings important data that can help future integrated metapopulation management plans that target genetic-based translocation and reintroduction actions.
Matrilineal structure of ex situ and in situ populations of the black lion tamarin (Leontopithecus chrysopygus Mikan, 1823) and insights for its management
Keywords: Diversidade genética; DNA mitocondrial; Leontopithecus chrysopygus; Genetical diversity; Mitochondrial DNA; CIENCIAS BIOLOGICAS::GENETICA; CIENCIAS BIOLOGICAS